The Politics of Knowledge Production and Decolonisation: An Appraisal of Mahmood Mamdani’s Contributions - Sifiso Ndlovu (The Thinker)
One of the fundamental challenges facing higher education is the much-needed confrontation of the legacies of colonialism which are hidden behind the claims of universality, neutrality and objectivity in knowledge production. From the vantage point of the present, Mahmood Mamdani, is one of the scholars who have given an account of colonial rule, its main characteristics and consequences of colonial conquests in a telling manner that renders transparent how the universalising structure of political modernity produced the colonised as subjects of difference. In his writings, Mamdani has connected the diverse experiences of the post-colonial world and flagged modernity as very pivotal in understanding the politics of knowledge production because it was crafted by the colonial project which centred on producing colonial subjects of difference within the hegemonic European thought. Mamdani’s main contribution is his use of historical analysis from the vantage point of the present to offer a productive frame of thought on knowledge production that exposes the anatomy and operation of colonialism and its universalising structures that have been inadvertently normalised as the model in knowledge production. In this article, I attempt to piece together the fundamentals of Mamdani’s exposition of how colonialism was a particular variation of the discourse of difference that shaped forms of existence and knowing. Primarily using a decolonial inspired theoretical framework, the paper makes a nuanced reading of Mamdani’s writings to show how his contributions makes visible the impact of colonialism as a project that is not confined to history and its pervasiveness in shaping the production of the objects of knowledge and its subjects.